Examining student perceptions of an inter-institutional interprofessional stroke simulation activity. Issue 3 (4th May 2018) - Pinto, Casey; Possanza, Anthony; Karpa, Kelly
ABSTRACT: Integration of interprofessional educational (IPE) activities into health professions' curricula aims to promote collaborative practice with a goal of improving patient care. An interprofessional stroke simulation involving standardised patients was organised for IPE student learners from a number of different health professions programmes based across several different institutions. In this article, we describe the development of an inter-institutional IPE activity and examine the outcomes of this activity on student interprofessional growth. Using a pre-post-study design, all participants were invited to anonymously respond to the 16-question IPEC Competency Self-Assessment tool to examine self-assessed interprofessional interactions and values as a result of the simulation. The questionnaire was available to the students using an online platform, and paired t-tests were used to analyse the responses. Quantitative data revealed significant positive changes in both the values and interaction domains of the assessment from pre- to post-simulation experience ( p < 0.0001 and p = 0.0003, respectively). Student reflections identified new realisations around the concepts of leadership and team member roles in the context of patient care. Results of this endeavour support the effectiveness of this activity for developing interprofessional competencies among students, suggest that the self-assessment tool may be used as a means to detect these changes, and lend support to our methods for establishing inter-institutional IPE partnerships.